The Effectiveness of Experimental Diet with Varying Levels of Papain on The Growth Performance, Survival Rate and Feed Utilization of Keureling Fish (Tor tambra) - Muchlisin, Zainal Abidin; Afrido, Fardin; Murda, Tanzil; Fadli, Nur; Muhammadar, Abdullah A.; Jalil, Zulkarnain; Yulvizar, Cut (Biosaintifika: Journal of Biology & Biology Education, 2016)
The objective of present study was to determine the optimum level of papain in the diet of keureling fish (Tor tambra). The complete random design was utilized in this study. Six levels of papain dosage were tested in triplicates, i.e. 0 (control); 17.5 mg kg-1, 20.0 mg kg-1, 22.5 mg kg-1, 25.0 mg kg-1 and 27.5 mg kg-1 of feed. The experimental fish were fed the experimental diet two times a day at 8 AM and 5 PM at feeding level of 5% body weight for 90 days. The Anova test result showed that papain enzyme gave a significant effect on the weight gain, daily growth rate, specific growth rate, survival rate, feed conversion ratio and feed efficiency (P<0.05). The Duncan multi-rage test result showed that the higher values for all measured parameters were obtained at the dosage of 27.5 mg kg-1. Therefore, it is concluded that the optimum dosage of papain enzyme for keureling fish was 27.5 mg kg-1 of feed.How to CiteMuchlisin, Z. A., Afrido, F., Murda, T., Fadli, N., Muhammadar, A. A., Jalil, Z., & Yulvizar, C. (2016). The Effectiveness of Experimental Diet with Varying Levels of Papain on The Growth Performance, Survival Rate and Feed Utilization of Keureling Fish (Tor tambra). Biosaintifika: Journal of Biology & Biology Education, 8(2), 172-177.